Development of Sensory Quality and Shelf Life of Dried Noodles Using Catfish Flour and Mocaf: An Alternative Supplementary Feeding Prototype - Laras Sitoayu; Harna Harna; Mertien Sa'pang; Putri Ronitawati; Dian Puspita Sari (Media Publikasi Cendekia Indonesia, 2026)
Chronic Energy Deficiency (CED) in pregnant women remains a substantial problem in developing countries, including Indonesia, year by year. The main cause of CED is insufficient intake during pregnancy. One effective solution is providing additional food, such as supplementary feeding (pemberian makanan tambahan/PMT), to pregnant women. It is important to develop innovative PMT options that can serve as alternatives to combat CED. This research aimed to replace traditional ingredients with catfish and Mocaf flour for sensory testing and to evaluate the shelf life of dry noodles as an alternative PMT for pregnant women with CED. The study used a laboratory experimental approach with a Completely Randomized Design (CRD) . This study tested four formulations combining mocaf, catfish, and wheat flour: F0 (0%:0%:100%), F1 (20%:5%:70%), F2 (30%:10%:60%), and F3 (35%:15%:50%). Sensory evaluation analysis used a Likert Scale, with 25 semi-trained panellists, with scale of 1-4. Data were analyzed using ANOVA followed by Duncan’s post hoc test with SPSS version 23. The results indicated that the substitution significantly affected color preference (p < 0.05). The optimal formulation was F2, with 10% catfish flour and 30% Mocaf flour. Most variables, such as taste, aroma, and texture, suggest that F2 is preferred more than the other formulas. Based on the results of the nutritional value calculations for the selected Formula F2, it has nutritional content including energy of 399.63 kcal, carbohydrates of 56.15 g, fat of 10.10 g, and protein of 21.03 g. The developed dry noodle prototype is a promising nutrient-enriched food product.